Comprehensive Review of Geopolymer Concrete For 3-D Building Printing - ABDUL AZIZ, AIN NADRAH; SALLEH, NORHAFIZAH (Recent Trends in Civil Engineering and Built Environment, 2022)
The major goals for creating 3-D printed buildings are design flexibility, modification, efficiency, waste reduction, decreased workforce, and manufacturing complicated structures with less expensive materials. The most crucial features of a good 3-D printing are the fresh qualities of concrete. To sustain the succeeding layers of 3-D printing, concrete must have a high workability for extrusion, an optimal open time, and a high early strength. After a research that had been done, based on the results, there are a lot of factors that affecting geopolymer concrete properties such as the amount of activator and water-to-solid ratio. Geopolymer concrete were resulting more compressive strength at 8% activator content than in 10% activator content. The highest compressive strength can go up 26.30% times more than 25 grade concrete which was only 31 MPa with Fly-ash content 30% of the mixture. The workability of geopolymer concrete was also founded that the factor of activator concentration and water/ash ratio affecting the workability. It resulting based on water/ash ratio, the flow can go up to 120% with 0.16 water/ash ratio. While, the higher the NaOH concentration, the lower the workability. Extrudability, flowability, buildability, strength between layers, aggregates, and the water-cement ratio were all considered as control aspects of concrete for 3-D printing. Manufacturers of 3-D building printing materials that use ecologically beneficial ingredients can automatically contribute to the creation of a sustainable environment, according to the findings of this study.